PENETAPAN KADAR RUTIN PADA EKSTRAK ETANOL DAUN PIDADA MERAH (Sonneratia caseolaris) DENGAN KLT DENSITOMETER - Lestari, Dwi; Syamsul, Eka Siswanto; Mentari, Ika Ayu (Jurnal Riset Kefarmasian Indonesia, 2024)
Red pidada leaves (Sonneratia caseolaris L) which is a species of mangrove plant that can grow in rivers and has been widely used as a natural medicine. Red Pidada leaves are often used by the people of East Kalimantan as a cold powder and wound remover. This study aims to determine the routine content of red pidada leaf extract. The research included extraction by maceration, routine assay using a TLC densitometer, phytochemical screening and validation of methods determined by parameters including: linearity and precision. A mixture of butanol-ethyl acetate-formic acid-asor (5:5:2:1) was chosen as the mobile phase. The results of this research for the maximum routine wavelength are 265 nm. The linearity test obtained from the regression function is y = 151.6 + 80.88x with a correlation coefficient (r) and Vxo of 0.97566 and 0.842% respectively. The concentration of routine in the extract was 1.9215±0.028%